Is rashism a form of fascism? Comparison of definitions - Kwiatkowski, Sebastian (The Copernicus Journal of Political Studies, 2025)
The article aims to compare the concept of “rashism” with fascism. The term “rashism” gained popularity after the Russian invasion of Ukraine and is understood as a synthesis of the “Russian spirit” with fascism, which is believed to be the cause of the aggressive and imperial policies of the Russian Federation. By reviewing the proposed definitions of rashism, alongside definitions of fascism and fascist source texts, and examining Vladimir Putin’s speeches, the article concludes with a critical assessment that challenges the validity of the rashism concept.